Energy conservation and greenhouse gas mitigation under different production systems in rice cultivation. (1st July 2017) - Chaudhary, V.P.; Singh, K.K.; Pratibha, G.; Bhattacharyya, Ranjan; Shamim, M.; Srinivas, I.; Patel, Anurag
Abstract: Identification of a suitable cultivation method with low energy use, GWP and high productivity is the need of the hour. A 16-year old field study in the Indo-Gangetic Plains (IGP) with different methods of rice cultivation viz., zero tillage (ZT), happy turbo seeder (HTS), bed planting (BP), reduced tillage (RT), conventional sowing (CS), direct sowing (DS), broadcast method of sowing (BS), manual transplanting (HT) and selected transplanting methods like, manual transplanter (MT) and mechanical transplanter (MaT) was used to evaluate the energy input and GWP. HT method of rice cultivation recorded higher energy use than ZT, HTS, BP, RT, CS, DS and BS methods, respectively. Whereas HTS method recorded highest net grain energy (NEg) and this was followed by ZT and MaT, The PTR method recorded 61–66% higher GWP compared with direct sown unpuddled method of rice cultivation. Among direct sown unpuddled methods of rice cultivation, HTS, BP, RT and ZT had lower GWP than farmers' practice. MaT recorded higher carbon output than ZT, HTS, BP, RT, CS, DS and BS methods. The study indicated that direct seeded method of rice cultivation is energy efficient with lower GWP and thus may be recommended. Highlights: The Energy use and GHG emissions of different rice establishment methods is analysed. Transplanted puddled rice (TPR) had lower EUE over direct sown method (DSR). TPR recorded higher total C input, lower CSI over DSR due to higher fuel use. TPR had higher GHG emissions due to higher CH4 emissions, fuel use and fertilizer.